Perbandingan Informasi Citra Potongan Axial T2 Antara Turbo Spin Echo (TSE) Dengan Half-Fourier Aquisition Single-Shot Turbo Spin Echo (HASTE) Pada Pemeriksaan Magnetic Resonance Cholangiopancreatography (MRCP) - Adilfi Amalia Yuniar; Dartini Dartini; Rasyid Rasyid; Bagus Dwi Handoko; Nanang Sulaksono (Jurnal Imejing Diagnostik (JImeD), 2021)
Backgroud: MRCP is a non-invasive imaging examination, which is used for the evaluation of biliary tract, pancreatic duct, and gallbladder. Pulse sequences which can be used to visualize organs in MRCP on T2 weighting is using a fast pulse sequences such as sequences TSE or Haste. The purpose of this research was to knowing the difference image information between T2 axial TSE with Haste and where better to use between the two sequences on axial T2 MRCP examination.Methods: This type of research is experimental observational approach, it has been carried out in the best MRI 1.5 Tesla at RSU Haji Surabaya. Sample used were 5 patients. Each patient performed two pieces of axial T2 sequences in which the TSE and Haste. Furthermore, the image submitted to the three doctors radiologist to fill out a questionnaire that has been provided to assess the image consisting of the liver, gallbladder, common bile duct (CBD), pancreas, intrahepatic duct and an assessment of the artifacts.Results: The results of analytical assessment Wilcoxon test, for the entire anatomy with ρ value of 0.002 which means that ρ 0.05, and the artifacts show the ρ value of 0.006, which means ρ 0.05. This proves that there are differences in image information between T2 axial TSE with T2 axial Haste the MRCP examination. At each of anatomy, liver has ρ value of 0,071 (ρ 0.05), gallbladder has ρ value of 0.317 (ρ 0.05), CBD has ρ value of 0.003 (ρ 0.05), pancreas has ρ value of  0.014 (ρ 0.05) and intrahepatic duct has ρ value of 0.004  (ρ 0.05). Based on the mean rank statistical test results show sequence Haste better in generating image information on the whole anatomy, but in each of anatomy based on the mean rank of gallbladder both sequences are equally good in showing gallbladder, whereas to display the liver, CBD, pancreas, and intrahepatic duct, the results showed T2 Haste mean rank better, it is because it has the characteristics of high Haste T2 signal intensity and better in reducing motion artifacts.Conclusion: Wilcoxon test analysis results expressed Ha accepted, meaning that there is a difference between the image information pieces axial T2 TSE with Haste the MRCP examination. The mean rank shows Haste superior to TSE, this is because the artifacts on TSE and therefore contributes to the respondent's assessment, other than that Haste has a high signal intensity so that it can show more clearly ducts.